The welfare costs of rent-seeking: a methodologically individualist and subjectivist revision - Michael Makovi (Editura ASE Bucuresti, 2015)
Gordon Tullock is acknowledged for being the first to recognize the true costs of rent-seeking as including not only the Harberger triangle but also the Tullock rectangle. This rectangle does not constitute merely a lossless transfer of wealth, but it causes a misallocation of resources as rent-seekers invest resources in lobbying. However, a close reading of Tullock’s writings shows that his arguments are formulated in a holistic fashion, speaking of what is efficient or inefficient for society. Rent-seeking is inefficient because it reduces societal welfare. But according to a methodologically individualist and subjectivist economics, such a claim is invalid. We must distinguish between positive economic fact and normative moral philosophy. We call for a reconstruction of utility and welfare economics based on methodological individualism and subjectivism with implications for the theories of monopoly and competition: practices which Neoclassical perfect-competition theory considers to be evidence of rent-seeking should instead be deemed as indications of genuine competition Political economy should be concerned with ascertaining which institutions will best enable individuals to pursue their individually subjective ends – or else economists should be explicit about their normative preferences and political philosophies.